Il progetto di Tele-università e l’Istituto Universitario Europeo di Firenze - Vedovato, Giuseppe (Rivista di studi politici internazionali, 2008)
ABSTRACT - The Author examines the case for a Tele-University, an offshoot of the idea of European University with ideological roots going back to the Congress of the Hague in 1948. Together with other eminent scholars, in the 1960s, the Author himself drew up a plan for a Tele-University, based on the experience of national university centres, but with a more communitarian slant. Having been assigned this task by the Consultative Assembly of the Council of Europe, he formed a plan for an institution that would transcend national identity and be based on recent technological advances in communications, with its seat in Florence. After being accepted by the Committee for Higher Education and Research, the project for an Interuniversity European Institute for Distance Teaching was accepted by the Parliamentary Assembly of the Council of Europe on 26 October 1971. Whereas the plan was received enthusiastically by many well-known professors and by the main European cultural associations, it encountered the resistance of European, Italian and Florentine bureaucrats, and was further weighed down by profound forms of nationalism and specific commercial expectations that were in no way inspired by the necessary European spirit. The Author had to fight with the Italian Parliament (as well as against the local administration) to try to soften the frigid ‘economic’ prejudice of the Italians in preventing the removal of bureaucratic impediments; whereas in the European Parliament his battle to find support for the European inspiration of the project enjoyed the full approval of the international community, it was again impeded by many obstacles. The project was left in an unfinished state, but this did not prevent those who had supported it from working towards its realization, with widespread support, because it would hasten the consolidation of a shared European culture. RÉSUMÉ - L’Auteur reconstitue les vicissitudes de la Télé-université européenne, destinée à approfondir le concept d’Université Européenne idéalement issu du Congrès de La Haye de 1948. A la fin des années soixante, Vedovato imagina, avec d’éminents spécialistes, la création d’une université européenne à distance sur le modèle de certains centres nationaux mais avec une empreinte communautaire. Chargé de ce projet par l’Assemblée Consultative du Conseil de l’Europe, il formula l’hypothèse d’une institution, qui dépasserait les spécificités nationales, s’appuierait sur les progrès techniques en matière de communication et serait située à Florence. Formellement reconnu par le Comité de l’Enseignement supérieur et de la Recherche, le projet d’Institut Universitaire Européen pour la promotion de la formation à distance fut accueilli le 26 octobre 1971 par l’Assemblée Parlementaire du Conseil de l’Europe. Malgré l’enthousiasme d’illustres professeurs et de grandes associations culturelles pro-européennes, le projet dut faire face à des freins bureaucratiques à la fois européens, italiens et florentins qui mirent en évidence des nationalismes bien enracinés et des attentes commerciales dépourvues de l’esprit européen. Vedovato dut se battre sur trois fronts pour vaincre les obstacles: au niveau parlementaire italien pour débloquer la rigueur économique de l’administration; au niveau local pour lever les contraintes bureaucratiques et au niveau du Parlement Européen pour faire triompher l’esprit communautaire. Malgré le soutien de la communauté scientifique internationale, il n’y parvint pas. Le projet resta inachevé. Toutefois, l’initiative de Vedovato de proposer un modèle européen de pédagogie universitaire, aujourd’hui amplement partagé, fait encore son chemin car il porrai accélérer la construction et le partage de la culture européenne.